Hairiness Gene Regulated Multicellular, Non-Glandular Trichome Formation in Pepper Species - Liu, Jinqiu; Wang, Haoran; Liu, Mengmeng; Liu, Jinkui; Liu, Sujun; Cheng, Qing; Shen, Huolin (Frontiers in Plant Science, 2021)
Trichomes are unicellular or multicellular epidermal structures that play a defensive role against environmental stresses. Although unicellular trichomes have been extensively studied as a mechanistic model, the genes involved in multicellular trichome formation are not well understood. In this study, we first classified the trichome morphology structures in Capsicum species using 280 diverse peppers. We cloned a key gene (Hairiness) on chromosome 10, which mainly controlled the formation of multicellular non-glandular trichomes (type II, III, and V). Hairiness encodes a Cys2-His2 zinc-finger protein, and virus-induced gene silencing of the gene resulted in a hairless phenotype. Differential expression of Hairiness between the hairiness and hairless lines was due to variations in promoter sequences. Transgenic experiments verified the hypothesis that the promoter of Hairiness in the hairless line had extremely low activity causing a hairless phenotype. Hair controlled the formation of type I glandular trichomes in tomato, which was due to nucleotide differences. Taken together, our findings suggest that the regulation of multicellular trichome formation might have similar pathways, but the gene could perform slightly different functions in crops.